Sense of Community dan Self-Regulated Learning sebagai Prediktor pada Prokrastinasi Akademik Mahasiswa - Effy Wardati Maryam; Ghozali Rusyid Affandi; Vanda Rezania (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2019)
Academic procrastination in students is a determining factor for the success of students in completing their studies. Engagement with the community and the ability of students to organize themselves in learning also play a role in academic procrastination. This study aims to determine the relationship of Sense of Community (SoC) and Self -Regulated Learning (SRL) with Academic Procrastination. The population of this study was all UMSIDA students in the odd semester of 2018-2019 academic year with the total number of 9824 students and the total sample based on Isaac and Michael's table with an 5% error rate were 385 students with a proportioned random sampling technique. Research data collection used three psychological scales, namely the scale of academic procrastination, the scale of the sense of community, and the scale of self-regulated learning. Analysis of research data used was product moment correlation and multiple regression analysis. The results of the analysis show that the Sense of Community and Self-Regulated Learning have a negative relationship with academic procrastination. If students perceive themselves to have a Sense of Community and high Self-Regulated Learning, they will tend to reduce their academic procrastination. However, the Self-Regulated Learning prediction on academic procrastination is higher than the Sense of Community on academic procrastination.